2018
DOI: 10.1038/s41433-018-0061-z
|View full text |Cite
|
Sign up to set email alerts
|

Cellular regeneration strategies for macular degeneration: past, present and future

Abstract: Despite considerable effort and significant therapeutic advances, age-related macular degeneration (AMD) remains the commonest cause of blindness in the developed world. Progressive late-stage AMD with outer retinal degeneration currently has no proven treatment. There has been significant interest in the possibility that cellular treatments may slow or reverse visual loss in AMD. A number of modes of action have been suggested, including cell replacement and rescue, as well as immune modulation to delay the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
74
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 207 publications
0
74
0
Order By: Relevance
“…It has been estimated that 285 million people are affected by visual impairment globally, with retinal diseases accounting for approximately 26% of blindness . Many inherited and age‐related retinal dystrophies culminate in the loss of photoreceptors . There are currently no treatments to reverse this degeneration, thus cell replacement has become a prerequisite on the path toward therapeutic transplantations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been estimated that 285 million people are affected by visual impairment globally, with retinal diseases accounting for approximately 26% of blindness . Many inherited and age‐related retinal dystrophies culminate in the loss of photoreceptors . There are currently no treatments to reverse this degeneration, thus cell replacement has become a prerequisite on the path toward therapeutic transplantations.…”
Section: Introductionmentioning
confidence: 99%
“…There are currently no treatments to reverse this degeneration, thus cell replacement has become a prerequisite on the path toward therapeutic transplantations. The derivation of human embryonic stem cells (hESCs) in 1998 and induced pluripotent stem cells (hiPSCs) in 2007 has provided the much needed breakthrough as both cell types can be expanded indefinitely in vitro as well as being able to generate photoreceptors and retinal pigment epithelium (RPE) . The subsequent development of protocols to derive three‐dimensional retinal organoids from hESCs/hiPSCs demonstrated that structures akin to the developing eye and laminated retina arise and many retinal cell types are produced .…”
Section: Introductionmentioning
confidence: 99%
“…Overall, there are an estimated over 30 million blind and partially sighted people in Europe with an average of 1 in 30 individuals experiencing sight loss. The major causes of blindness are cataracts, glaucoma, and age‐related macular degeneration . The latter accounts for 50% of blind and partially sighted registration with an estimated prevalence of ∼600,000 significantly visually impaired people in the U.K. and over 8 million worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a massive effort in recent years to differentiate RPE from human pluripotent stem cells for use in transplantation studies, and different groups reported encouraging morphological and functional results in animal models of retinal degeneration after transplantation of RPE cells, as nicely reviewed recently Leach and Clegg, 2015;Nazari et al, 2015). Based on studies in animals, clinical trials for macular degeneration have started with the idea to replace the lost or dysfunctional RPE in AMD patients with healthy RPE cells derived from ESCs or iPSCs (Chichagova et al, 2018;Dalkara et al, 2016). First phase I/II trials sponsored by Astellas Pharma (formerly Ocata Therapeutics) were launched to evaluate the safety and tolerability of a subretinal injection of human ESC-derived RPE as cell suspension in patients with advanced dry AMD and Stargardt's disease (Mehat et al, 2018;Schwartz et al, 2015;Song et al, 2015).…”
Section: Therapeutic Strategies For Photoreceptor Degenerative Diseasesmentioning
confidence: 99%